Analisis penerimaan dan penyetoran Pajak Bumi dan Bangunan Perdesaan dan Perkotaan (PBB-P2) di Desa Tombasian Atas Kecamatan Kawangkoan Barat - Momongan, Intan Valeri Gisela; Pangerapan, Sonny; Datu, Christian V (Riset Akuntansi dan Portofolio Investasi, 2024)
The Rural and Urban Land and Building Tax (or PBB-P2) is a crucial source of revenue for local governments in Indonesia. This research will analyze the revenue collection and payment of PBB-P2 in Tombasian Village, Kawangkoan Barat Subdistrict. The research methodology employed a qualitative approach, gathering data through interviews with tax officials and secondary data analysis. The findings clearly show a low level of public awareness regarding tax obligations, which is hurting tax revenue. Public understanding of tax policies and the quality of tax services significantly influence the payment of PBB-P2. The study provides recommendations to local governments to enhance public awareness campaigns, empower tax officials, and improve services to the community, thereby increasing revenue collection and tax payment of PBB-P2. These measures will undoubtedly lead to an increase in local tax revenue, which will support the development of Tombasian Village.